The Role of the Timurid Dynasty in the History of Uzbekistan (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The role of the Temur dynasty in the political and cultural development of Uzbekistan is analyzed in the article. Amir Temur and his descendants made great achievements in science, art, state management and turned Samarkand into a cultural center. The importance of Timurid heritage in today’s history and culture is highlighted.